The dual role of tissue regulatory T cells in tissue repair: return to homeostasis or fibrosis - Zhang, Peiyan; Wang, Jiawei; Miao, Jinlin; Zhu, Ping (Frontiers in Immunology, 2025)
Tissue resident regulatory T cells (tissue Tregs) are vital for maintaining immune homeostasis and controlling inflammation. They aid in repairing damaged tissues and influencing the progression of fibrosis. However, despite extensive research on how tissue Tregs interact with immune and non-immune cells during tissue repair, their pro- and anti-fibrotic effects in chronic tissue injury remain unclear. Understanding how tissue Tregs interact with various cell types, as well as their roles in chronic injury and fibrosis, is crucial for uncovering the mechanisms behind these conditions. In this review, we describe the roles of tissue Tregs in repair and fibrosis across different tissues and explore potential strategies for regulating tissue homeostasis. These insights hold promise for providing new perspectives and approaches for the treatment of irreversible fibrotic diseases.